Effects of NB-UVB with pimecrolimus cream on the expression of eotaxin in serum and CCR3 on peripheral blood monocytes in patients with adult atopic dermatitis - Yan YANG; Jia-yan LI; Xin ZHOU; Xin TIAN; Ai-li GAO; Si-ying XIONG; Wei LI; Xiao-yin CHEN; Yu-mei LIU; Hui-lan ZHU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To compare expression levels of eotaxin in the serum and CCR3 on the peripheral blood monocytes (PBMC) prior to and after the treatment with NB-UVB plus pimecrolimus cream, in order to elucidate the pathogenesis of atopic dermatitis(AD). Methods: Serum level of eotaxin was detected by enzym-linked immunosorbent assay (ELISA) in 30 adult patients with AD prior to and after the treatment. CCR3 expression on the peripheral blood monocytes was analyzed by flow cytometry. Results: Treatment of AD with NB-UVB plus pimecrolimus cream markedly lowered the serum levels of eotaxin [(133.86±42.23) pg/mL vs. (101.54±35.63) pg/mL, P<0.01], and CCR3 on PBMC [(23.10±6.31)% vs. (16.52±6.59)%, P<0.01]. Conclusions: Combination of NB-UVB with pimecrolimus cream could decrease the expression levels of eotaxin and CCR3, resulting in a reduction in recruitment and activation of eosinophils, consequently leading to improvement of AD. This study also suggested that combination of NB-UVB with pimecrolimus cream is safe and effective for AD.